Building Sector: Stimulus Packages Make an Impact - Martin Gornig; Sebastian Weber (Weekly Report, 2010)
The sharp slump of the German economy has left its mark on the building sector. Commercial construction has been especially affected by the significant decline in companies' propensity to invest - triggered by the macroeconomic downturn. However, due to the stable development of real wages and the overall labour market as well as targeted supporting programmes, the recession has more or less bypassed residential construction. Public sector construction even increased in 2009, most notably during the later half of the year when the effects of the second stimulus package came into force. Nevertheless, due to idle capacities in commercial construction, only moderate price increases are to be expected. Overall - and in real terms - , 2009 will see little change in German construction volumes compared to the previous year. In 2010, stimulus packages will encourage a noticeable recovery, which - in turn - will have a positive effect on the country's overall economy. All in all, construction volumes are expected to grow by more than two per cent (adjusted for price) in 2010 and the main construction industry will profit disproportionately. From an economic point of view, the investment programmes thus meet their intended goal: stabilisation of the construction sector.
Keywords: L74; O11; 330; Housing demand; Construction industry; Forecast 2010